MODEL MANAJEMEN PEMASARAN PENDIDIKAN DALAM MENINGKATKAN MINAT PESERTA DIDIK BARU DI MI MA’ARIF AL FATTAH KEPIRANG WONOSOBO - -, Ismail; Muntaqo, Rifqi; Muntaqo, Lutfan (Ta'dib (Jurnal Ilmiah Pendidikan dan Peradaban Islam), 2025)
This study explores the implementation of educational marketing management in increasing the interest of new student enrollment at MI Ma’arif Al Fattah Kepirang. The research focuses on the following questions: (1) How is educational marketing management implemented at MI Ma’arif Al Fattah Kepirang to attract new students? (2) What is the marketing management model applied to enhance student enrollment interest? (3) What are the supporting and inhibiting factors in implementing educational marketing strategies at the school? Using a qualitative descriptive approach, the research was conducted at MI Ma’arif Al Fattah Kepirang. Data were collected through observation, interviews, and documentation. Informants were selected through a process involving data collection, reduction, presentation, and verification. Data credibility was ensured through triangulation and reference sufficiency, while dependability and confirmability were maintained through supervisor auditing. The findings indicate that educational marketing management at MI Ma’arif Al Fattah Kepirang has been well-implemented, reaching approximately 90% effectiveness. Key strategies used to increase new student interest include building a strong school image, implementing public relations programs, and applying the marketing mix approach. Supporting factors include the school's strategic location, affordable tuition, and qualified teaching staff. Conversely, inhibiting factors consist of limited educational funding and inadequate facilities and infrastructure.